The influence of temperature on Pacific hake co‐occurrence with euphausiids in the California Current Ecosystem. (13th January 2023) - Phillips, Elizabeth M.; Malick, Michael J.; Gauthier, Stéphane; Haltuch, Melissa A.; Hunsicker, Mary E.; Parker‐Stetter, Sandra L.; Thomas, Rebecca E.
Abstract: Understanding the influence of ocean conditions on predator–prey relationships can provide insight for ecosystem‐based fisheries management. Pacific hake ( Merluccius productus ) are abundant and commercially important groundfish in the California Current Ecosystem (CCE) that consume euphausiids (krill) as a major prey item. We used data from the biennial joint U.S.‐Canada Integrated Ecosystem & Acoustic Trawl Survey for Pacific hake (2007–2019, n = 8 surveys) to quantify co‐occurrence of age 2+ hake with krill in relation to bottom depth, continental shelf break location, surface chlorophyll‐a, and 100‐m temperature. Vertical distributions of hake varied among years and were not correlated to krill depth. Hake hotspots occurred primarily off the Oregon coast and near Cape Mendocino, while most krill hotspots occurred in the northern CCE. The probability of co‐occurrence was greatest during cool ocean conditions (100‐m temperature 1°C below average), averaging 41.0% and extending throughout most of the CCE. During warm ocean conditions (100‐m temperature 1°C above average), predicted co‐occurrence averaged 17.0% and was concentrated near Cape Mendocino. These results indicate that hake‐krill co‐occurrence is a function of predator and prey spatial distributions and overall krill abundance. Furthermore, temperature influences hake‐krill co‐occurrence and may explain some of the variation in hake growth and recruitment to the fishery.